Signature Panel of 11 Methylated mRNAs and 3 Methylated lncRNAs for Prediction of Recurrence-Free Survival in Prostate Cancer Patients - Cai J; Yang F; Chen X; Huang H; Miao B (Dove Medical Press, 2021)
Jiarong Cai,1,* Fei Yang,1,* Xuelian Chen,1 He Huang,2 Bin Miao3 1Department of Urology, the Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, 510630, People's Republic of China; 2General Surgery Department, the Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, 510630, People's Republic of China; 3Department of Organ Transplantation, the Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, 510630, People's Republic of China*These authors contributed equally to this workCorrespondence: He HuangGeneral Surgery Department, the Third Affiliated Hospital of Sun Yat-sen University, No. 600, Tianhe Road, Guangzhou, Guangdong, 510630, People's Republic of ChinaEmail huangh85@mail.sysu.edu.cnBin MiaoDepartment of Organ Transplantation, the Third Affiliated Hospital of Sun Yat-Sen University, No. 600, Tianhe Road, Guangzhou, Guangdong, 510630, People's Republic of ChinaTel +86-20-82179517Fax +86-20-82179517Email miaobin@mail.sysu.edu.cnBackground: Radical prostatectomy is the main treatment for prostate cancer (PCa), a common cancer type among men. Recurrence frequently occurs in a proportion of patients. Therefore, there is a great need to early screen those patients to specifically schedule adjuvant therapy to improve the recurrence-free survival (RFS) rate. This study aims to develop a biomarker to predict RFS for patients with PCa based on the data of methylation, an important heritable contributor to carcinogenesis.Methods: Methylation expression data of PCa patients were downloaded from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus database (GSE26126), and the European Bioinformatics Institute (E-MTAB-6131). The stable co-methylation modules were identified by weighted gene co-expression network analysis. The genes in modules were overlapped with differentially methylated RNAs (DMRs) screened by MetaDE package in three datasets, which were used to screen the prognostic genes using least absolute shrinkage and selection operator analyses. The prognostic performance of the prognostic signature was assessed by survival curve analysis.Results: Five co-methylation modules were considered preserved in three datasets. A total of 192 genes in these 5 modules were overlapped with 985 DMRs, from which a signature panel of 11 methylated messenger RNAs and 3 methylated long non-coding RNAs was identified. This signature panel could independently predict the 5-year RFS of PCa patients, with an area under the receiver operating characteristic curve (AUC) of 0.969 for the training TCGA dataset and 0.811 for the testing E-MTAB-6131 dataset, both of which were higher than the predictive accuracy of Gleason score (AUC = 0.689). Also, the patients with the same Gleason score (6- 7 or 8- 10) could be further divided into the high-risk group and the low-risk group.Conclusion: These results suggest that our prognostic model may be a promising biomarker for clinical prediction of RFS in PCa patients.Keywords: prostate cancer, recurrence-free survival, methylation, prognostic signature